Colonialism and development in Africa - Leander Heldring; James A. Robinson (African Economic History Network (AEHN), 2013)
In this paper we evaluate the impact of colonialism on development in Sub-Saharan Africa. In the world context, colonialism had very heterogeneous effects, operating through many mechanisms, sometimes encouraging development sometimes retarding it. In the African case, however, this heterogeneity is muted, making an assessment of the average effect more interesting. We emphasize that to draw conclusions it is necessary not just to know what actually happened to development during the colonial period, but also to take a view on what might have happened without colonialism and also to take into account the legacy of colonialism. We argue that in the light of plausible counter-factuals, colonialism probably had a uniformly negative effect on development in Africa. To develop this claim we distinguish between three sorts of colonies: (1) those which coincided with a pre-colonial centralized state, (2) those of white settlement, (3) the rest. Each have distinct performance within the colonial period, different counter-factuals and varied legacies.
Keywords: F54; N37; N47; O55; 330; Colonialism; Africa; colonial legacy; inequality; development; institutions